A large, single‐center, real‐world study of clinicopathological characteristics and treatment in advanced ALK‐positive non‐small‐cell lung cancer. (4th April 2017) - Chen, Gang; Chen, Xi; Zhang, Yaxiong; Yan, Fang; Fang, Wenfeng; Yang, Yunpeng; Hong, Shaodong; Miao, Siyu; Wu, Manli; Huang, Xiaodan; Luo, Youli; Zhou, Cong; et al.
Abstract: Crizotinib has achieved astonishing success in advanced non‐small‐cell lung cancer (NSCLC) patients harboring anaplastic lymphoma kinase (ALK) rearrangement. However, no real‐world studies described the clinicopathological characteristics and treatment of such patients in China. Patients were consecutively collected from Sun Yat‐sen University Cancer Center. Chi‐square test was applied to explore the relationship between ALK fusion status and metastasis sites. Kaplan–Meier methods and multivariable analyses were used to estimate progression‐free survival (PFS). A total of 291 advanced NSCLC patients (ALK (+), N  = 97; both ALK & epidermal growth factor receptor (EGFR) (‐), N  = 194) were enrolled. The occurrence of brain metastasis in ALK‐positive patients was significantly higher than double‐negative ones both at baseline (26.5% vs. 16.5%, P  = 0.038) and during treatment (25.8% vs. 11.9%, P  = 0.003), but opposite for pleural effusion (6.2% vs. 26.9%, P  < 0.001 at baseline; 3.1% vs. 10.3%, P  = 0.031 during treatment). ALK‐positive patients of 53.6% used crizotinib, whereas others only received chemotherapy (37.1%) or supportive care (9.3%). Usage of crizotinib prolonged PFS compared with chemotherapy in ALK‐positive patients (median PFS 17.6 m vs. 4.8 m, P  < 0.001). ALK‐positive NSCLC had more brain metastasis and less pleural effusion than double‐negative ones. Crizotinib showed better PFS than chemotherapy in advanced ALK‐positive NSCLC at any line. However, half advanced ALK‐positive patients never received crizotinib, which was grim and need improving. Abstract : Our real‐world study confirmed that patients harboring ALK rearrangement tended to be younger at diagnosis, and more of them were nonsmokers and adenocarcinoma compared with those without ALK rearrangement and epidermal growth factor receptor (EGFR) mutation. Besides, ALK‐positive NSCLC had more brain metastasis and less pleural effusion than double‐negative ones. Moreover, crizotinib showed better PFS than chemotherapy in advanced ALK‐positive NSCLC, which should be recommended, especially as first‐line choice. However, almost half of advanced ALK‐positive patients did not take crizotinib, which reflected a serious situation in the treatment of ALK‐positive NSCLC in China.